Secondary battery and electronic device

CN122315276BActive Publication Date: 2026-10-20XIAMEN AMPACE TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610756787.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-20
Estimated Expiration
2046-05-28

AI Technical Summary

Technical Problem

但是,上述技术难以兼顾隔膜与极片之间的粘结强度和离子传输速率,并且对于高能量密度的锂离子电池而言,在其整形过程中容易出现松散、变形等问题,增大了极片局部析锂以及锂离子电池内部短路的风险,进而导致锂离子电池的直流电阻(DCR)增大以及循环性能降低

Benefits of technology

[0018]本申请提供了一种二次电池和电子装置,通过对正极材料层的压实密度ρ、厚度T、正极极片的层数N以及隔膜中粘结层的面密度W建立上述关系式,能够根据电极组件中正极极片的设计选择与之匹配的隔膜粘结层面密度,较好地平衡正极极片与隔膜之间界面的稳定性以及离子传输速率,从而能够在兼顾二次电池体积能量密度的同时,提高正极极片与隔膜之间粘结力,降低二次电池的直流电阻增长率并提高二次电池的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122315276B_ABST
    Figure CN122315276B_ABST
Patent Text Reader

Abstract

The application provides a secondary battery and an electronic device, which comprise a positive electrode sheet and a separator; the number of layers of the positive electrode sheet is N layers along the thickness direction of the electrode assembly, 20≤N≤85; the positive electrode sheet comprises a positive electrode material layer, the compaction density of the positive electrode material layer is ρ g / cm 3 , 2.2≤ρ≤2.8, the thickness of the positive electrode material layer is T μm, 20≤T≤180; the separator comprises a bonding layer, the area density of the bonding layer is W g / m 2 ; S=ρ×ln(N+1)×T, I=1 / (ρ×T), 0.00167S+0.0167I+0.0167≤W≤0.005S+0.067I+0.05 are met. Through the above setting, the adhesion between the positive electrode sheet and the separator can be improved, the direct current resistance growth rate of the secondary battery can be reduced and the cycle performance of the secondary battery can be improved while the volume energy density of the secondary battery is considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a secondary battery and electronic device. Background Technology

[0002] With the increasing demands for energy density, safety performance, and long cycle life of lithium-ion batteries from electric vehicles and energy storage systems, the stability of the internal interfaces of lithium-ion batteries has become a key limiting factor, with the interface between the electrode and the separator being particularly important. Currently, the industry commonly improves the stability of the interface between the separator and the electrode by coating the separator with an adhesive layer (using binders such as polyvinylidene fluoride (PVDF) or polymethyl methacrylate (PMMA)) and hot-pressing processes. However, these technologies struggle to balance the bonding strength and ion transport rate between the separator and the electrode. Furthermore, for high-energy-density lithium-ion batteries, problems such as loosening and deformation can easily occur during the shaping process, increasing the risk of localized lithium plating on the electrode and internal short circuits in the lithium-ion battery. This, in turn, leads to increased DC resistance (DCR) and reduced cycle performance. Summary of the Invention

[0003] The purpose of this application is to provide a secondary battery and electronic device that, while taking into account the volumetric energy density of the secondary battery, improves the adhesion between the electrode and the separator, reduces the DC resistance growth rate of the secondary battery, and improves the cycle performance of the secondary battery.

[0004] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0005] The first aspect of this application provides a secondary battery comprising an electrode assembly, the electrode assembly including a positive electrode and a separator; the positive electrode has N layers along its thickness direction, where 20 ≤ N ≤ 85; the positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector, the compaction density of the positive electrode material layer being ρ g / cm³. 3 2.2≤ρ≤2.8, the thickness of the positive electrode material layer is T μm, 20≤T≤180; the separator includes a substrate and an adhesive layer disposed on at least one surface of the substrate, the areal density of the adhesive layer is W g / m³. 2The following conditions must be met: S = ρ × ln(N + 1) × T, I = 1 / (ρ × T), 0.00167S + 0.0167I + 0.0167 ≤ W ≤ 0.005S + 0.067I + 0.05. Where S is the interfacial stress coefficient and I is the ion transport requirement coefficient. By adjusting the secondary battery to meet the above characteristics, it is possible to improve the adhesion between the positive electrode and the separator while maintaining the volumetric energy density of the secondary battery, thereby reducing the DC resistance growth rate and improving the cycle performance of the secondary battery.

[0006] In one or more embodiments of this application, 344 ≤ S ≤ 1780. By adjusting the value of S within the above range, the interfacial stress coefficient has a suitable value. The separator adhesive layer further matches the compaction density ρ, thickness T, and number of layers N of the positive electrode material layer. This is beneficial for better matching the accumulation of interfacial shear stress between the positive electrode and the separator, reducing the risk of delamination failure between the electrode and the separator, and simultaneously improving the adhesion between the electrode and the separator, thus improving the interfacial stability between the positive electrode and the separator. Therefore, while considering the volumetric energy density of the secondary battery, it is beneficial to improve the adhesion between the electrode and the separator, reduce the DC resistance growth rate of the secondary battery, and improve the cycle performance of the secondary battery.

[0007] In one or more embodiments of this application, 0.002 ≤ I ≤ 0.009. By adjusting the value of I within the above range, the ion transport coefficient has a suitable value, the separator adhesive layer further matches the compaction density ρ and thickness T of the positive electrode material layer, and there is a better lithium-ion transport efficiency between the positive electrode sheet and the separator, which is beneficial to reducing the DC resistance growth rate of the secondary battery and improving the cycle performance of the secondary battery.

[0008] In one or more embodiments of this application, 0.9 ≤ W ≤ 6. By adjusting the value of W within the above range, the separator adhesive layer has a suitable areal density, which is beneficial for better balancing the interfacial stress coefficient and ion transport coefficient. This further matches the compaction density ρ, thickness T, and number of positive electrode layers N of the positive electrode material layer, and better balances the stability of the interface between the positive electrode and the separator as well as the ion transport rate. This is beneficial for improving the adhesion between the positive electrode and the separator while maintaining the volumetric energy density of the secondary battery, reducing the DC resistance growth rate of the secondary battery, and improving the cycle performance of the secondary battery.

[0009] In one or more embodiments of this application, the porosity of the separator is φ1, where 20% ≤ φ1 ≤ 60%. By adjusting the porosity of the separator within the above range, the separator has a suitable porosity, which further matches the compaction density of the positive electrode material layer. This provides more bonding points for the separator and the positive electrode material layer, which is beneficial for improving the adhesion between the positive electrode and the separator. Simultaneously, the suitable porosity is conducive to higher ion transport efficiency between the positive electrode and the separator. Therefore, while maintaining the volumetric energy density of the secondary battery, it is beneficial to improve the adhesion between the positive electrode and the separator, reduce the DC resistance growth rate of the secondary battery, and improve the cycle performance of the secondary battery.

[0010] In one or more embodiments of this application, the adhesive layer includes an adhesive, which includes at least one of polyvinylidene fluoride, polymethyl methacrylate, styrene-butadiene rubber, polyacrylate, or lithium poly(4-styrene sulfonate); based on the mass of the adhesive layer, the mass percentage content of the adhesive is w1, where 97.5% ≤ w1 ≤ 99.5%. By controlling the type and mass percentage content of the adhesive within the above range, the adhesive layer has suitable adhesive strength, which is beneficial for better balancing the stability of the interface between the positive electrode and the separator, and for better improving the adhesion between the positive electrode and the separator.

[0011] In one or more embodiments of this application, the positive electrode material layer includes a positive electrode active material, which includes lithium iron phosphate. At least a portion of the surface of the lithium iron phosphate is provided with a carbon material layer. Based on the mass of the lithium iron phosphate, the mass percentage of the carbon material layer is w2, where 0.5% ≤ w2 ≤ 2.5%. By controlling the mass percentage of the carbon material layer within the above range, the lithium iron phosphate surface is coated with a carbon material layer of suitable mass, which is beneficial to improving the lithium-ion transport efficiency of the lithium iron phosphate. This, in turn, improves the rate performance of the secondary battery, reduces the DC resistance growth rate of the secondary battery, and simultaneously improves the cycle performance of the secondary battery.

[0012] In one or more embodiments of this application, the separator includes a ceramic coating disposed on at least one side of the substrate, with the ceramic coating located between the adhesive layer and the substrate. By providing the ceramic coating, on the one hand, it is beneficial to improve the mechanical strength of the separator and reduce the risk of lithium dendrite puncture short circuits; on the other hand, the ceramic coating helps to increase the surface particle size of the separator, providing more bonding points for the positive electrode and the separator, and the ceramic coating helps to better match the accumulation of interfacial shear stress between the positive electrode and the separator, thereby improving the adhesion between the positive electrode and the separator.

[0013] In one or more embodiments of this application, the ceramic coating comprises ceramic particles, which include at least one of alumina, boehmite, silicon oxide, magnesium oxide, titanium oxide, calcium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. Based on the mass of the ceramic coating, the mass percentage of ceramic particles is w3, where 60% ≤ w3 ≤ 95%. By controlling the type and mass percentage of ceramic particles within the above range, it is beneficial to further improve the mechanical strength of the separator and reduce the risk of lithium dendrite puncture short circuit. In addition, by using the above-mentioned ceramic particles, the ceramic coating has a microporous structure, which, while ensuring good lithium-ion transport efficiency, is beneficial to improve the electrolyte wetting rate, thereby improving the adhesion between the positive electrode and the separator while better improving the cycle performance of the secondary battery.

[0014] In one or more embodiments of this application, the positive electrode material layer includes a solid electrolyte, which includes at least one of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, or lithium aluminum titanium phosphate. Based on the mass of the positive electrode material layer, the mass percentage of the solid electrolyte is w4, where 1% ≤ w4 ≤ 5%. By controlling the type and mass percentage of the solid electrolyte within the above range, the positive electrode material layer contains a suitable mass of solid electrolyte. The solid electrolyte has good lithium-ion transport performance and electronic insulation performance, which is beneficial for the positive electrode material layer to have good lithium-ion transport efficiency while reducing the risk of internal short circuits. This allows for a reduction in the DC resistance growth rate of the secondary battery and an improvement in the cycle performance of the secondary battery while maintaining the volumetric energy density of the secondary battery.

[0015] In one or more embodiments of this application, the porosity of the substrate is φ2, 30% ≤ φ2 ≤ 70%. By controlling the porosity of the substrate within the above range, the substrate has a suitable porosity. A suitable porosity is beneficial for achieving higher ion transport efficiency between the positive electrode and the separator, thereby improving the electrolyte wetting rate. This helps to reduce the DC resistance growth rate of the secondary battery and improve its cycle performance while maintaining the volumetric energy density of the secondary battery.

[0016] A second aspect of this application provides an electronic device that includes the secondary battery found in any of the foregoing embodiments. Therefore, the electronic device provided by this application has good performance.

[0017] The beneficial effects of this application are:

[0018] This application provides a secondary battery and an electronic device. By establishing the above-mentioned relationship between the compaction density ρ, thickness T, number of positive electrode layers N, and areal density W of the adhesive layer in the separator, the adhesive layer density of the separator can be selected to match the design of the positive electrode in the electrode assembly. This better balances the stability of the interface between the positive electrode and the separator and the ion transport rate. As a result, while taking into account the volumetric energy density of the secondary battery, the adhesion between the positive electrode and the separator can be improved, the DC resistance growth rate of the secondary battery can be reduced, and the cycle performance of the secondary battery can be improved.

[0019] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0021] Figure 1 This is a schematic diagram of the winding structure formed by the electrode assembly in one embodiment of this application;

[0022] In the figure, electrode assembly 001; positive electrode 10; positive current collector 11; positive electrode material layer 12; negative electrode 20; negative current collector 21; negative electrode material layer 22; separator 30; substrate 31; adhesive layer 32. Detailed Implementation

[0023] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0024] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.

[0025] With the increasing demands for volumetric energy density, safety performance, and long cycle life of lithium-ion rechargeable batteries, the compaction density of electrodes is constantly pushing the limits, while the number of electrode layers is also continuously increasing. Maintaining the stability of the internal interfaces of lithium-ion batteries has become crucial, especially the interface between the electrode and the separator. Specifically, the adhesion between the electrode and the separator gradually weakens as the electrode compaction density and the number of layers increase. Furthermore, after the electrode and separator coatings are bonded, deformation and loosening of the openings are prone to occur during the rechargeable battery shaping process, increasing the risk of localized lithium plating on the electrode and internal short circuits in the lithium-ion battery. Currently, the common practice is to coat the separator with an adhesive layer and use a hot-pressing process to bond the separator and the electrode to improve the interfacial stability between the electrode and the separator. However, this technology can lead to low porosity and poor ion transport performance when the adhesive layer is too thick or the coating weight is too heavy. This results in increased internal resistance and decreased rate performance of the secondary battery. Furthermore, during the charging and discharging process of high-capacity secondary batteries, as the number of winding layers increases, the active material in the electrode will undergo a certain volume change under high compaction density, causing the accumulation of interfacial shear stress between the electrode and the separator, which easily increases the risk of delamination failure between the electrode and the separator. Based on this, this application provides a secondary battery and electronic device that, while maintaining the volumetric energy density of the secondary battery, improves the adhesion between the electrode and the separator, reduces the rate of increase in DC resistance of the secondary battery, and improves the cycle performance of the secondary battery. The specific technical solution is as follows:

[0026] This application provides a secondary battery, including an electrode assembly comprising a positive electrode and a separator. Along the thickness direction of the electrode assembly, the positive electrode has N layers, where 20 ≤ N ≤ 85. For example, the value of N can be 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or a range consisting of any two of the above values. The range of N can be 20 to 85, 25 to 80, 30 to 75, 35 to 70, and all such ranges and sub-ranges. The positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The compaction density of the positive electrode material layer is ρ g / cm³. 32.2 ≤ ρ ≤ 2.8, for example, the value of ρ can be 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.8 or any range of two of the above values. The value range of ρ can be 2.2 to 2.8, 2.25 to 2.7, 2.3 to 2.65, 2.35 to 2.6, 2.4 to 2.55, and all ranges and sub-ranges thereof; the thickness of the positive electrode material layer is T. μm, 20≤T≤180; for example, the value of T can be 20, 40, 60, 80, 100, 120, 140, 160, 180, or a range consisting of any two of the above values. The range of T can be 20 to 180, 40 to 160, 60 to 140, 80 to 120, and all such ranges and sub-ranges; the diaphragm includes a substrate and an adhesive layer disposed on at least one surface of the substrate, the areal density of the adhesive layer being W g / m³. 2 The following conditions must be met: S = ρ × ln(N + 1) × T, I = 1 / (ρ × T), 0.00167S + 0.0167I + 0.0167 ≤ W ≤ 0.005S + 0.067I + 0.05. Where S is the interfacial stress coefficient and I is the ion transport requirement coefficient.

[0027] For example, see Figure 1 The electrode assembly has a wound structure, and the winding direction of the electrode assembly is defined as the W direction. The wound electrode assembly 001 includes a positive electrode 10, a negative electrode 20, and a separator 30. The positive electrode 10 includes a positive current collector 11 and a positive electrode material layer 12 disposed on two surfaces of the positive current collector 11; the negative electrode 20 includes a negative current collector 21 and a negative electrode material layer 22 disposed on two surfaces of the negative current collector 21; the separator 30 includes a substrate 31 and an adhesive layer 32 disposed on two surfaces of the substrate 31.

[0028] The inventors discovered that by establishing the above-mentioned relationship between the compaction density ρ, thickness T, number of positive electrode layers N, and areal density W of the adhesive layer in the separator, the appropriate separator adhesive layer areal density can be selected based on different positive electrode designs in the electrode assembly. Specifically, on the one hand, by using the compaction density ρ, thickness T, and number of layers N, the interfacial stress coefficient S generated by the volume change of the positive electrode active material during cycling in a secondary battery using a corresponding specification of positive electrode is obtained. This is beneficial for better matching the accumulation of interfacial shear stress between the positive electrode and the separator, and reducing the stress on the electrode and the separator. On the one hand, the risk of layer failure is mitigated; on the other hand, the ion transport coefficient I between the positive electrode and the separator is obtained by using the compaction density ρ and thickness T, which enables better lithium-ion transport efficiency between the positive electrode and the separator, thus reducing the DC resistance growth rate of the secondary battery and improving its cycle performance. Then, based on the interfacial stress coefficient S and the ion transport coefficient I, the areal density W of the separator adhesive layer within a suitable range corresponding to the specifications of the positive electrode is selected, ensuring appropriate adhesion force and facilitating a better balance between the stability of the interface between the positive electrode and the separator and the ion transport rate. Specifically, when the number of layers N of the positive electrode is too small, for example less than 20, the capacity of the secondary battery is low, its practical application scenarios are limited, and it is difficult to meet the requirements. When the number of layers N of the positive electrode is too large, for example greater than 85, it is difficult to complete the welding of the secondary battery, requiring higher production processes. Therefore, by controlling the secondary battery to meet the above characteristics, it is possible to improve the adhesion force between the positive electrode and the separator, reduce the DC resistance growth rate, and improve the cycle performance of the secondary battery while maintaining the volumetric energy density of the secondary battery.

[0029] In this application, it is understood that a single turn of the positive electrode in a wound electrode assembly refers to a turn of the positive electrode, starting from one end and ending at the end of one full rotation along the winding direction of the electrode assembly, with the starting and ending points aligned in the thickness direction of the electrode assembly. In this application, the starting point of the first turn of the positive electrode is the starting end of the positive electrode material layer on the positive electrode, and so on. In this application, a single turn of the positive electrode comprises two layers, i.e., two layers of positive electrode in each turn along a radial direction perpendicular to the winding axis of the electrode assembly. In a stacked electrode assembly, the number of positive electrode layers is the same as the number of positive electrode sheets in the electrode assembly.

[0030] In this application, "a positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a part of the surface of the positive electrode current collector. This application has no particular limitation, as long as the purpose of this application can be achieved.

[0031] In one or more embodiments of this application, the adhesive layer is disposed only on the surface of the substrate facing the positive electrode. By disposing of the adhesive layer on the surface of the substrate facing the positive electrode, the adhesive layer helps to better match the accumulation of interfacial shear stress between the positive electrode and the separator, thereby improving the adhesion between the positive electrode and the separator. Furthermore, single-sided coating helps to reduce manufacturing costs. It also helps to better balance the stability of the interface between the positive electrode and the separator and the ion transport rate, thereby reducing the DC resistance growth rate of the secondary battery and improving the cycle performance of the secondary battery. In other embodiments, the adhesive layer may be disposed on the surface of the substrate facing the negative electrode, or no adhesive layer may be disposed there.

[0032] In one or more embodiments of this application, 344 ≤ S ≤ 1780. For example, the value of S can be 344, 350, 400, 600, 800, 1000, 1200, 1400, 1600, 1700, 1780, or a range consisting of any two of the above values. The value range of S can be 344 to 1780, 350 to 1700, 400 to 1600, 600 to 1400, 800 to 1200, and all such ranges and sub-ranges. By adjusting the value of S within the above range, the interfacial stress coefficient has a suitable value. The membrane adhesive layer further matches the compaction density ρ, thickness T, and number of layers N of the positive electrode material layer. This is beneficial for better matching the interfacial shear stress accumulation between the positive electrode and the membrane, reducing the risk of delamination failure between the electrode and the membrane, and simultaneously improving the adhesion between the electrode and the membrane, thus improving the interfacial stability between the positive electrode and the membrane. This helps to improve the adhesion between the electrode and the separator while taking into account the volumetric energy density of the secondary battery, thereby reducing the DC resistance growth rate of the secondary battery and improving the cycle performance of the secondary battery.

[0033] In one or more embodiments of this application, 0.002 ≤ I ≤ 0.009. For example, the value of I can be 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, or a range consisting of any two of the above values. The value range of I can be 0.002 to 0.009, 0.003 to 0.008, 0.004 to 0.007, 0.005 to 0.006, and all such ranges and sub-ranges. By adjusting the value of I within the above range, the ion transport coefficient has a suitable value, the membrane adhesive layer further matches the compaction density ρ and thickness T of the positive electrode material layer, and there is a better lithium-ion transport efficiency between the positive electrode sheet and the membrane, which is beneficial to reducing the DC resistance growth rate of the secondary battery and improving the cycle performance of the secondary battery.

[0034] In one or more embodiments of this application, 0.9 ≤ W ≤ 6. For example, the value of W can be 0.9, 1.0, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, or a range consisting of any two of the above values. The range of W can be 0.9 to 6, 1.0 to 5.5, 1.5 to 5, 2 to 4.5, 2.5 to 4, and all such ranges and sub-ranges. By adjusting the value of W within the above range, the separator adhesive layer has a suitable areal density, which is beneficial for better balancing the interfacial stress coefficient and the ion transport coefficient. This further matches the compaction density ρ, thickness T, and number of positive electrode layers N of the positive electrode material layer, and better balances the stability of the interface between the positive electrode and the separator as well as the ion transport rate. This is beneficial for improving the adhesion between the positive electrode and the separator while taking into account the volumetric energy density of the secondary battery, reducing the DC resistance growth rate of the secondary battery, and improving the cycle performance of the secondary battery.

[0035] In one or more embodiments of this application, the porosity of the separator is φ1, where 20% ≤ φ1 ≤ 60%. For example, the value of φ1 can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a range consisting of any two of the above values. The range of φ1 can be 20% to 60%, 25% to 55%, 30% to 50%, 35% to 45%, and all ranges and sub-ranges thereof. By adjusting the porosity of the separator within the above range, the separator has a suitable porosity, which further matches the compaction density of the positive electrode material layer, providing more bonding points for the separator and the positive electrode material layer. This is beneficial for improving the adhesion between the positive electrode and the separator, while the suitable porosity also contributes to higher ion transport efficiency between the positive electrode and the separator. Therefore, it is beneficial to improve the adhesion between the positive electrode and the separator while maintaining the volumetric energy density of the secondary battery, reducing the DC resistance growth rate of the secondary battery, and improving the cycle performance of the secondary battery.

[0036] In one or more embodiments of this application, the adhesive layer includes an adhesive, which includes at least one selected from polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), styrene-butadiene rubber, polyacrylate, or lithium poly(4-styrene sulfonate). Based on the mass of the adhesive layer, the mass percentage of the adhesive is w1, where 97.5% ≤ w1 ≤ 99.5%. For example, the value of w1 can be 97.5%, 97.7%, 98%, 98.1%, 98.3%, 98.5%, 98.7%, 99%, 99.1%, 99.3%, 99.5%, or a range consisting of any two of the above values. The range of w1 can be 97.5% to 99.5%, 97.7% to 99.3%, 98% to 99.1%, 98.1% to 99%, and all ranges and subranges thereof. By adjusting the type and mass percentage of the binder within the above range, the adhesive layer has suitable adhesion, which is beneficial to better balance the stability of the interface between the positive electrode and the separator, and better improve the adhesion between the positive electrode and the separator.

[0037] This application does not impose any particular limitation on the weight-average molecular weight of the adhesive, as long as it can achieve the purpose of this application. For example, the weight-average molecular weight of the adhesive can be 5 × 10⁻⁶. 4 Up to 1.5×10 6 .

[0038] In one or more embodiments of this application, the positive electrode material layer includes a positive electrode active material, which includes lithium iron phosphate. At least a portion of the surface of the lithium iron phosphate is provided with a carbon material layer. Based on the mass of the lithium iron phosphate, the mass percentage of the carbon material layer is w2, where 0.5% ≤ w2 ≤ 2.5%. For example, the value of w2 can be 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, 2.5%, or a range consisting of any two of the above values. The range of w2 can be 0.5% to 2.5%, 0.7% to 2.3%, 0.9% to 2.1%, 1.1% to 1.9%, 1.3% to 1.7%, and all ranges and sub-ranges thereof. By selecting lithium iron phosphate as the positive electrode active material and controlling the mass percentage of the carbon material layer within the above range, lithium iron phosphate, as a nano-sized particle, has more complex surface physical properties. When lithium iron phosphate is selected as the positive electrode active material, as the compaction density increases, the van der Waals force and friction coefficient of the lithium iron phosphate surface layer are further reduced. At the same time, the lithium iron phosphate surface is coated with a carbon material layer of appropriate mass, which is beneficial to improving the lithium-ion transport efficiency of lithium iron phosphate. Thus, while improving the rate performance of the secondary battery and reducing the DC resistance growth rate of the secondary battery, the cycle performance of the secondary battery is also improved.

[0039] In one or more embodiments of this application, the mass percentage of lithium iron phosphate is 84% ​​to 99% based on the mass of the cathode material layer. By adjusting the mass percentage of lithium iron phosphate within the above range, lithium iron phosphate has a suitable mass percentage, which is beneficial for the secondary battery to have a suitable volumetric energy density and good rate performance, thereby improving the cycle performance of the secondary battery.

[0040] In one or more embodiments of this application, the separator includes a ceramic coating disposed on at least one side of the substrate, with the ceramic coating located between the adhesive layer and the substrate. By providing the ceramic coating, on the one hand, it is beneficial to improve the mechanical strength of the separator and reduce the risk of lithium dendrite puncture short circuits; on the other hand, the ceramic coating helps to increase the surface particle size of the separator, providing more bonding points for the positive electrode and the separator, and the ceramic coating helps to better match the accumulation of interfacial shear stress between the positive electrode and the separator, thereby improving the adhesion between the positive electrode and the separator.

[0041] In one or more embodiments of this application, the ceramic coating is disposed only on the surface of the substrate facing the positive electrode. By disposing of the ceramic coating on the surface of the substrate facing the positive electrode, the ceramic coating helps to better match the accumulation of interfacial shear stress between the positive electrode and the separator, thereby better improving the adhesion between the positive electrode and the separator. In other embodiments, the surface of the substrate facing the negative electrode may be coated with a ceramic coating or may not be coated with a ceramic coating.

[0042] In one or more embodiments of this application, the ceramic coating comprises ceramic particles, which include at least one of alumina, boehmite, silicon oxide, magnesium oxide, titanium oxide, calcium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate; based on the mass of the ceramic coating, the mass percentage of ceramic particles is w3, where 60% ≤ w3 ≤ 95%. For example, the value of w3 can be 60%, 63%, 65%, 67%, 70%, 73%, 75%, 77%, 80%, 83%, 85%, 87%, 90%, 93%, 95%, or a range consisting of any two of the above values. The range of w3 can be 60% to 95%, 63% to 93%, 65% to 90%, 67% to 87%, 70% to 85%, and all such ranges and sub-ranges. By controlling the type and mass percentage of ceramic particles within the above range, it is beneficial to further improve the mechanical strength of the separator and reduce the risk of lithium dendrite puncture short circuit. In addition, by using the above-mentioned ceramic particles, the ceramic coating has a microporous structure, which, while taking into account good lithium-ion transport efficiency, is beneficial to improve the electrolyte wetting rate, thereby improving the adhesion between the positive electrode and the separator and improving the cycle performance of the secondary battery.

[0043] In one or more embodiments of this application, the positive electrode material layer includes a solid electrolyte, which includes at least one of polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), or lithium aluminum titanium phosphate (LATP). Based on the mass of the positive electrode material layer, the mass percentage of the solid electrolyte is w4, where 1% ≤ w4 ≤ 5%. For example, the value of w4 can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of the above values. The range of w4 can be 1% to 5%, 1.5% to 4.5%, 2% to 4%, 2.5% to 3.5%, and all ranges and subranges thereof. By controlling the type and mass percentage of the solid electrolyte within the above range, the cathode material layer contains a suitable mass of solid electrolyte. The solid electrolyte has good lithium-ion transport performance and electronic insulation performance, which is beneficial for the cathode material layer to have good lithium-ion transport efficiency while reducing the risk of internal short circuits. Thus, while taking into account the volumetric energy density of the secondary battery, it is possible to reduce the DC resistance growth rate of the secondary battery and improve the cycle performance of the secondary battery.

[0044] In this application, the chemical formula of lithium aluminum titanium phosphate (LATP) is Li. 1+x Al x Ti 2-x (PO4)3, where 0 < x < 2, specifically, for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1.4 Al 0.4 Ti 1.6 (PO4)3.

[0045] In one or more embodiments of this application, the porosity of the substrate is φ2, 30% ≤ φ2 ≤ 70%. For example, the value of φ2 can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or a range consisting of any two of the above values. The range of φ2 can be 30% to 70%, 35% to 65%, 40% to 60%, 45% to 55%, and all such ranges and sub-ranges. By controlling the porosity of the substrate within the above range, the substrate has a suitable porosity. A suitable porosity is beneficial for achieving higher ion transport efficiency between the positive electrode and the separator, and for improving the electrolyte wetting rate. This is beneficial for reducing the DC resistance growth rate of the secondary battery and improving its cycle performance while maintaining the volumetric energy density of the secondary battery.

[0046] In this application, the adhesive layer further includes a dispersant and a thickener. Based on the mass of the adhesive layer, the mass percentage of the dispersant is 0.3% to 1.5%, and the mass percentage of the thickener is 0.2% to 1%. Specifically, the dispersant may include at least one of sodium polyacrylate (PAA-Na), ammonium polyacrylate (PAA-NH4), polyacrylic acid (PAA), tributyl phosphate, or butyl polyacrylate, and the thickener may include at least one of carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose (HPMC), cross-linked polyacrylic acid (carbomer), or alkali-swellable polyacrylic acid copolymers.

[0047] In this application, the ceramic coating further includes a ceramic coating binder, a dispersant, a thickener, and a wetting agent. Based on the mass of the ceramic coating, the mass percentage of the ceramic coating binder is 4.4% to 39.4%, the mass percentage of the dispersant is 0.3% to 1%, the mass percentage of the thickener is 0.2% to 0.8%, and the mass percentage of the wetting agent is 0.1% to 0.5%. Specifically, the dispersant may include at least one of sodium polyacrylate (PAA-Na) or ammonium polyacrylate (PAA-NH4), and the binder may include at least one of styrene-butadiene rubber (SBR), acrylate emulsion, polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP). The thickener includes carboxymethyl cellulose (CMC). The wetting agent may include at least one of polyether-modified polysiloxane or fatty alcohol polyoxyethylene ether.

[0048] The preparation method of the diaphragm is not particularly limited in this application. As long as it can achieve the purpose of this application, it is acceptable. For example, in one or more embodiments of this application, the preparation method of the diaphragm includes, but is not limited to, the following steps: (1) preparing adhesive layer slurry and ceramic coating slurry; (2) coating the ceramic coating slurry on one surface of the substrate, drying it, coating the adhesive layer slurry on the surface of the ceramic coating away from the substrate, drying it, and obtaining a single-sided coated semi-finished diaphragm; (3) repeating the above steps on the other surface of the substrate to obtain a double-sided coated finished diaphragm.

[0049] In some other possible embodiments, the preparation of the diaphragm includes, but is not limited to, the following steps: (1) preparing an adhesive layer slurry; (2) coating the adhesive layer slurry onto one surface of the substrate and then drying it; (3) repeating the above steps on the other surface of the substrate to obtain a double-coated finished diaphragm.

[0050] In some other possible embodiments, the preparation of the diaphragm includes, but is not limited to, the following steps: (1) preparing an adhesive layer slurry and a ceramic coating slurry; (2) coating the ceramic coating slurry on the surface facing the positive electrode, drying it, coating the adhesive layer slurry on the surface of the ceramic coating away from the substrate, drying it to obtain a single-sided coated semi-finished diaphragm; (3) coating the adhesive layer slurry on the other surface of the substrate, drying it to obtain a double-sided coated finished diaphragm.

[0051] This application does not impose any particular restrictions on the method of controlling the compaction density, as long as it achieves the purpose of this application. For example, the compaction density of the cathode material layer can be controlled by adjusting the cold pressing pressure or the coating weight. Under the same conditions, increasing the cold pressing pressure increases ρ, and decreasing the cold pressing pressure decreases ρ. Alternatively, under the same conditions, increasing the coating weight increases ρ, and decreasing the coating weight decreases ρ.

[0052] This application does not impose any particular restrictions on the method of controlling the thickness T of the cathode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the cathode material layer can be controlled by adjusting the cold pressing pressure or the coating weight. Under the same conditions, increasing the cold pressing pressure decreases T, and decreasing the cold pressing pressure increases T. Alternatively, under the same conditions, increasing the coating weight increases T, and decreasing the coating weight decreases T.

[0053] This application does not impose any particular restrictions on the method of controlling the membrane porosity, as long as it achieves the purpose of this application. For example, the porosity of the adhesive layer can be controlled by adjusting the porosity of the substrate, the coating weight of the adhesive layer, or the coating weight of the ceramic coating. Under the same conditions, an increase in the porosity of the substrate increases φ1; a decrease in the porosity of the substrate decreases φ1; an increase in the coating weight of the adhesive layer decreases φ1; a decrease in the coating weight of the adhesive layer increases φ1; an increase in the coating weight of the ceramic coating decreases φ1; and a decrease in the coating weight of the ceramic coating increases φ1.

[0054] This application does not impose any particular restrictions on the method of controlling the density of the adhesive layer, as long as it achieves the purpose of this application. For example, the areal density of the adhesive layer can be controlled by increasing the coating weight. Under the same conditions, increasing the coating weight increases the areal density, and decreasing the coating weight decreases the areal density.

[0055] This application does not impose any particular restrictions on the method of controlling the porosity of the substrate, as long as it achieves the purpose of this application. For example, substrates with different porosities can be obtained by purchasing.

[0056] This application does not impose any particular restrictions on the method of controlling the mass percentage of the carbon material layer on the surface of lithium iron phosphate, as long as the purpose of this application can be achieved. For example, lithium iron phosphate with different carbon material layer contents can be obtained by purchase.

[0057] In this application, when the electrode assembly is a wound structure, and the size of the electrode remains unchanged, the number of layers of the electrode can be adjusted by controlling the specifications of the winding needle during winding.

[0058] This application does not impose any particular limitation on the positive electrode current collector, as long as it can achieve the purpose of this application. For example, it can include aluminum foil, aluminum alloy foil, or composite current collectors (such as aluminum-carbon composite current collectors). The positive electrode material layer may also include a conductive agent and a binder. This application does not impose any particular limitation on the types of conductive agents and binders, as long as they can achieve the purpose of this application. For example, the binder may include at least one of polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene-butadiene copolymer (styrene-butadiene rubber), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium carboxymethyl cellulose, or potassium carboxymethyl cellulose. The conductive agent may include at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, or graphene. The conductive carbon black may be at least one of acetylene black, Super P, or Ketjen black. The carbon nanotubes may be at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes. The carbon fibers may be at least one of vapor-grown carbon fibers (VGCF) or carbon nanofibers. Optionally, the positive electrode may further include a conductive layer located between the positive current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited and can be any conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. This application does not impose any particular limitation on the conductive agent and binder in the conductive layer; for example, it can be at least one of the conductive agents and binders described above in the positive electrode material layer.

[0059] In this application, the secondary battery further includes a negative electrode sheet, which comprises a negative electrode material layer disposed on at least one surface of the negative electrode current collector. In this application, "a negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire surface area of ​​the negative electrode current collector, or it can be a partial surface area of ​​the negative electrode current collector. This application has no particular limitation, as long as the purpose of this application is achieved.

[0060] This application does not impose any particular limitation on the negative electrode current collector, as long as it can achieve the purpose of this application. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collectors. For example, the composite current collector can be a lithium copper composite current collector, a carbon copper composite current collector, a nickel copper composite current collector, a titanium copper composite current collector, etc. The negative electrode material layer includes a negative electrode active material. This application does not impose any particular limitation on the negative electrode active material, as long as it can achieve the purpose of this application. For example, the negative electrode active material can include, but is not limited to, natural graphite, artificial graphite, mesophase micro carbon spheres, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, and spinel-structured lithiated TiO2-Li4Ti5O. 12 The negative electrode material layer may contain at least one of the following: a Li-Al alloy. The negative electrode material layer may also include a conductive agent and a binder. This application does not particularly limit the types of conductive agents and binders, as long as they achieve the purpose of this application. For example, it may contain at least one of the conductive agents and binders in the aforementioned positive electrode material layer. This application does not particularly limit the mass ratio of the negative electrode active material, conductive agent, and binder in the negative electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of this application is achieved. Optionally, the negative electrode sheet may also contain a conductive layer located between the negative electrode current collector and the negative electrode material layer. This application does not particularly limit the composition of the conductive layer; it may contain conductive layers commonly used in the art. For example, the conductive layer may include a conductive agent and a binder. This application does not particularly limit the conductive agents and binders in the conductive layer; for example, it may contain at least one of the conductive agents and binders in the aforementioned positive electrode material layer.

[0061] This application does not impose any particular limitation on the thickness of the negative electrode material layer, as long as the purpose of this application can be achieved. This application also does not impose any particular limitation on the thickness of the negative electrode current collector, as long as the purpose of this application can be achieved.

[0062] This application does not impose any particular limitation on the type of substrate, as long as it can achieve the purpose of this application. For example, the substrate can be a nonwoven fabric or composite membrane with a porous structure, and the material of the substrate can include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane can be used.

[0063] In this application, there are no particular limitations on the thickness of the diaphragm, as long as it can achieve the purpose of this application.

[0064] In this application, the secondary battery also includes an electrolyte, which comprises lithium salts and non-aqueous solvents. This application does not impose any particular limitation on the lithium salt, as long as it achieves the purpose of this application. For example, the lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), or lithium difluoroborate. This application does not impose any particular limitation on the content of lithium salts in the electrolyte, as long as it achieves the purpose of this application. This application does not impose any particular limitation on the non-aqueous solvent, as long as it achieves the purpose of this application. For example, the non-aqueous solvent may include, but is not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). The aforementioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), or vinyl ethylene carbonate (VEC). Fluorinated carbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The aforementioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. This application does not impose any particular limitation on the content of non-aqueous solvents in the electrolyte, as long as the purpose of this application is achieved.

[0065] This application does not impose any particular restrictions on the outer casing; any casing known in the art can be used, as long as it achieves the purpose of this application. For example, the outer casing can be a rigid casing or a flexible casing; wherein, the material of the rigid casing can be metal or rigid plastic, and this application does not limit the type of metal, and any metal casing known in the art can be used, as long as it achieves the purpose of this application; the flexible casing can be a metal plastic film, such as aluminum-plastic film, steel-plastic film, etc.

[0066] This application does not impose any particular limitation on the type of secondary battery, which may include any device in which an electrochemical reaction occurs. In this application, the secondary battery may include, but is not limited to: lithium metal secondary batteries, lithium-ion secondary batteries (lithium-ion batteries), lithium polymer secondary batteries, or lithium-ion polymer secondary batteries (lithium-ion polymer batteries), etc.

[0067] The preparation process of the secondary battery described in this application is well known to those skilled in the art, and this application has no particular limitations. For example, it may include, but is not limited to, the following steps: stacking a separator, a positive electrode, a separator, and a negative electrode in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery. Alternatively, overcurrent protection elements, conductive plates, etc., may be placed in the packaging bag as needed to prevent pressure rise and overcharging / discharging inside the secondary battery. Alternatively, stacking a positive electrode, a separator, and a negative electrode in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly in a housing; injecting electrolyte into the housing and sealing it to obtain a secondary battery. Alternatively, overcurrent protection elements, conductive plates, etc., may be placed in the housing as needed to prevent pressure rise and overcharging / discharging inside the secondary battery.

[0068] A second aspect of this application provides an electronic device that includes the secondary battery found in any of the foregoing embodiments. Therefore, the electronic device provided by this application has good performance.

[0069] This application does not specifically limit the type of electronic device; it can be any electronic device known in the prior art. In one or more embodiments of this application, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0070] Example

[0071] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.

[0072] Test methods and equipment:

[0073] Electrode assembly sampling:

[0074] At 25°C, the lithium-ion battery was charged to 3.6V at a constant current of 0.3C, then charged to 0.05C at a constant voltage of 3.6V until the current cutoff was reached. After standing for 15 minutes, it was discharged to 2.0V at a constant current of 0.3C. Subsequently, the discharged lithium-ion battery was disassembled under an argon atmosphere, the electrode assembly was removed, and the electrode assembly was soaked in dimethyl carbonate solvent for 2 hours and dried at 60°C for 1 hour to obtain the electrode assembly.

[0075] Unless otherwise specified, the following test methods shall be performed using the electrode assembly obtained in the above manner.

[0076] Compaction density test of the cathode material layer:

[0077] Disassemble the electrode assembly, remove the positive electrode sheet, and use a punching machine to punch a small circular sample with an area of ​​s from the positive electrode material layer of the positive electrode sheet. Weigh the sample as M1 and measure its thickness as t1 with a micrometer. Scrape the positive electrode material layer from any side of the positive electrode sheet and weigh it as M2. Measure its thickness as t2 with a micrometer. The compaction density of the positive electrode material layer is ρ=(M1-M2) / (t1-t2) / s.

[0078] Thickness test of positive electrode material layer:

[0079] Disassemble the electrode assembly, remove the positive electrode sheet, take pictures of the positive electrode sheet using a scanning electron microscope (SEM), export the images, and measure the thickness of the single-sided positive electrode material layer. For each set of embodiments, five different locations are selected for measurement, and the average value is taken to obtain the thickness T of the single-sided positive electrode material layer.

[0080] Areal density test of adhesive layer:

[0081] Electrode assemblies were obtained using the sampling method described above, and membrane samples were obtained by disassembling the electrode assemblies. Testing was then performed according to the following steps:

[0082] After cutting the diaphragm into small circular pieces with radius R, weigh them as m1. Scrape off the adhesive layer from both surfaces of the diaphragm and weigh the remaining sample as m2. Then, the surface density of the adhesive layer coating on the diaphragm is W = (m1 - m2) / (2πR). 2 ), the unit is g / m2 .

[0083] Porosity testing of the diaphragm and substrate:

[0084] Electrode assemblies were obtained using the above sampling method. The diaphragm was obtained by disassembling the electrode assemblies. The gas displacement method was used for testing. The diaphragm was punched with a mold to prepare diaphragm samples (those skilled in the art can select molds of common sizes and shapes in the field according to factors such as the size and shape of the test object and the requirements of the test equipment). The samples were divided into two groups. All coatings on the surface of the diaphragm of one group were scraped off to prepare a substrate sample. The true volume V0 of the sample was measured using a true density tester. The apparent volume V of the sample can be calculated by measuring the area and thickness of the sample. The percentage of the sample pore volume to the total volume is (V-V0) / V×100%. The porosity φ1 of the diaphragm and the porosity φ2 of the substrate can be obtained by measuring and calculating the diaphragm sample and the substrate sample respectively.

[0085] Test of carbon material layer content in lithium iron phosphate:

[0086] Lithium iron phosphate was tested according to the standard "Chemical Analysis Methods for Lithium Iron Phosphate - Part 4: Determination of Carbon Content - High Frequency Combustion Infrared Absorption Method" (YST1028.4-2015) to obtain the mass percentage content w2 of the carbon material layer in lithium iron phosphate.

[0087] Interface peel strength test:

[0088] Disassemble the electrode assembly, remove the negative electrode sheet, and scrape off the positive electrode material layer on the surface of the positive current collector away from the separator to obtain a separator and positive electrode sheet sample.

[0089] The interfacial peel strength between the diaphragm and the positive electrode was tested using a high-speed rail tensile testing machine, in accordance with the national standard "Test Method for Peel Strength of Adhesive Tape" (GB / T 2792-2014). The specific steps are as follows: The sample was cut into 20mm × 80mm test strips. A 20mm × 60mm double-sided adhesive strip was attached to a steel plate, and then the test strip was attached to the double-sided adhesive strip with the positive electrode current collector facing down. A 20mm × 70mm paper tape was connected to the test strip using double-sided adhesive, adhering it to the surface of the diaphragm to obtain the test sample. The test was performed using a dedicated diaphragm adhesion tensile testing machine (model QT-6203). The test sample is fixed on the test stage, the paper tape is folded upwards at 90° and fixed with a clamp, and then the tensile testing machine starts to pull the paper tape at a speed of 50 mm / min, with a tensile displacement of 50 mm. The tensile force-displacement curve is obtained, and the relatively flat section of the curve is selected to determine the tensile force. The peel strength of the sample group is calculated by dividing the tensile force by the sample width (perpendicular to the tensile force direction). After testing 4 parallel samples, the average peel strength of the 4 samples is taken to obtain the final result, that is, the interfacial peel force between the separator and the positive electrode, in N / m.

[0090] Cyclic capacity retention test:

[0091] At 25℃, the lithium-ion battery was charged at a constant current of 0.5C to 3.6V, then charged at a constant voltage of 3.6V to 0.05C, allowed to rest for 5 minutes, and then discharged at a constant current of 1C to 2.5V, allowed to rest for 5 minutes. This constitutes one charge-discharge cycle, and the discharge capacity of each cycle was recorded. The lithium-ion battery was subjected to 1000 cycles under the above conditions, and the discharge capacity was measured after each cycle. Cycle capacity retention (%) = (Capacity after 1000 discharge cycles / First discharge cycle capacity) × 100%.

[0092] DC internal resistance growth rate test:

[0093] The DC internal resistance test of lithium-ion batteries can be divided into the following steps: (1) The test temperature is 25℃. The lithium-ion battery in the example or comparative example is charged to 3.6V with a constant current of 0.5C and charged to 0.025C with a constant voltage of 3.6V. After standing for 30 minutes, it is discharged to 3.0V with a constant current of 0.2C. The cutoff capacity of this step is recorded as C2. (2) Then the lithium-ion battery is left to stand for 1 hour, charged to 3.6V with a constant current of 0.5C2 and charged to 0.025C2 with a constant voltage of 3.6V. After standing for 10 minutes, it is discharged to 4 hours with a constant current of 0.5C2. (3) Then the lithium-ion battery is left to stand for 1 hour and discharged for 10 seconds with a constant current of 0.1C2. (4) Then it is discharged for 1 second with a constant current of 1C2. The voltage before this step is recorded as V1 and the voltage after this step is recorded as V2. The DC internal resistance of 1 second at 50% SOC is (V1-V2) / 1C2. The process of steps (1) to (4) above is regarded as a charge-discharge cycle. Ten lithium-ion batteries in each example are subjected to the above charge-discharge cycle at 25°C. The number of charge-discharge cycles is used as the abscissa, and the 1s DC internal resistance at 50% SOC measured at the corresponding number of charge-discharge cycles is used as the ordinate. The above charge-discharge cycle is repeated for 350 cycles. The scatter plot of the 1s DC internal resistance at 50% SOC obtained in each charge-discharge cycle is fitted into a curve to obtain the DC internal resistance growth rate.

[0094] Example 1-1

[0095] <Preparation of the positive electrode>

[0096] The positive electrode active materials, including lithium iron phosphate (with a carbon material layer comprising 1.5% carbon material by mass), positive electrode binder polyvinylidene fluoride (PVDF), conductive agent Super P, and solid electrolyte polyethylene oxide, were mixed with N-methylpyrrolidone (NMP) at a solid mass ratio of 92:2.5:2.5:3. The mixture was stirred uniformly under vacuum to obtain a positive electrode material slurry with a solid content of 60 wt%. This slurry was then uniformly coated onto one surface of a 13 μm thick aluminum foil used as a positive electrode current collector and dried at 80 °C for 1 hour to obtain a single-sided coated positive electrode sheet. The coating weight of the positive electrode material layer was 385 mg / 1540.25 mm. 2 Then, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive electrode material. After cold pressing, cutting, and welding of electrode tabs, a positive electrode sheet with a size of 7600mm × 64mm is obtained. Based on the mass of the lithium iron phosphate coated with the carbon material layer, the mass percentage of the carbon material layer on the surface of the lithium iron phosphate is 1.5%, and the compaction density of the positive electrode material layer is 2.5 g / cm³. 3 The thickness of the single-sided positive electrode material layer is 100μm.

[0097] <Preparation of Negative Electrode Sheets>

[0098] Artificial graphite (negative electrode active material), styrene-butadiene rubber (binder), and acetylene black (conductive agent) were mixed in a mass ratio of 97.4:1.4:1.2. Deionized water was added as a solvent to prepare a slurry with a solid content of 45 wt%. The slurry was stirred evenly in a vacuum mixer to obtain the negative electrode slurry. The negative electrode slurry was uniformly coated onto one surface of a 6 μm thick copper foil current collector and dried at 120°C for 1 hour to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 230 mg / 1540.25 mm. 2 The above steps are then repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of negative electrode material. After drying at 120℃, it is cold-pressed, then cut and welded with tabs to obtain a negative electrode sheet with dimensions of 7842mm×67mm for later use. The thickness of the single-sided negative electrode material layer is 72μm, and the thickness of the prepared negative electrode sheet is 150μm.

[0099] <Preparation of the diaphragm>

[0100] The adhesive layer binder polyvinylidene fluoride, dispersant polyacrylic acid, and thickener carboxymethyl cellulose were mixed in a mass ratio of 98.5:0.9:0.6, and the solvent NMP was added. After vacuum stirring, the adhesive layer slurry was obtained.

[0101] The ceramic coating binder polyvinylidene fluoride, ceramic particles alumina (Al2O3), dispersant sodium polyacrylate, thickener carboxymethyl cellulose, and wetting agent fatty alcohol polyoxyethylene ether were mixed in a mass ratio of 23.6:75:0.6:0.5:0.3. The solvent NMP was added, and the mixture was stirred under vacuum until homogeneous to obtain the ceramic coating slurry.

[0102] A 5μm thick polyethylene substrate was used as the diaphragm substrate. A ceramic coating slurry was coated onto the substrate and dried at 80℃ for 1 hour. An adhesive layer slurry was then coated onto the ceramic coating and dried at 80℃ for 1 hour to obtain a single-sided coated diaphragm. The above steps were repeated on the other surface to obtain the finished diaphragm. The coating weight of the ceramic coating was 1.8 g / m². 2 The areal density of the adhesive layer is 3.5 g / m³. 2 After drying, a diaphragm is obtained.

[0103] <Preparation of Electrolyte>

[0104] In an environment with a water content of less than 10 ppm, dimethyl carbonate, diethyl carbonate, and ethylene carbonate were mixed in a mass ratio of 1:1:1 to obtain an organic solvent. Then, the electrolyte salt LiPF6 was added to the organic solvent and mixed thoroughly to obtain the electrolyte. Based on the mass of the electrolyte, the electrolyte salt comprised 12.5% ​​by mass, with the remainder being the organic solvent.

[0105] <Preparation of Lithium-ion Batteries>

[0106] The prepared positive electrode, separator, and negative electrode are stacked in the order of separator, negative electrode, separator, and positive electrode, with the separator positioned between the positive and negative electrode to act as a separator. The electrode assembly is then wound to obtain an electrode assembly. The number of layers N of the positive electrode is 45 along the thickness direction of the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag and dehydrated at 80°C. The electrolyte prepared above is then injected, and the battery undergoes vacuum sealing, settling, formation, degassing, and edge trimming to obtain a lithium-ion battery. The upper limit of the formation voltage is 3.6V, the formation temperature is 70°C, and the formation settling time is 2 hours.

[0107] Examples 1-2 to Examples 1-3

[0108] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1. Among them, when the number of layers N of the positive electrode sheet changes, the specifications of the positive electrode sheet remain unchanged. By adjusting the specifications of the winding needle during winding, the number of layers N of the positive electrode sheet is as shown in Table 1.

[0109] Examples 1-4 to Examples 1-5

[0110] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1. Among them, the compaction density ρ of the positive electrode sheet is achieved by adjusting the coating weight of the positive electrode material layer, as shown in Table 1.

[0111] Examples 1-6 to Examples 1-7

[0112] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1. Specifically, the thickness T of the cathode material layer is adjusted by controlling the coating weight, as shown in Table 1.

[0113] Examples 1-8 to Examples 1-9

[0114] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1. Among them, when the number of layers N of the positive electrode sheet changes, the specifications of the positive electrode sheet remain unchanged. By adjusting the specifications of the winding needle during winding, the number of layers N of the positive electrode sheet is as shown in Table 1; by adjusting the coating weight of the positive electrode material layer, the compaction density ρ and the thickness T of the positive electrode material layer are as shown in Table 1.

[0115] Examples 1-10

[0116] Except for the steps in <Preparation of the diaphragm> to prepare the diaphragm, the rest is the same as in Example 1-1:

[0117] The adhesive layer binder polyvinylidene fluoride, dispersant polyacrylic acid, and thickener carboxymethyl cellulose were mixed in a mass ratio of 98.5:0.9:0.6, and the solvent NMP was added. After vacuum stirring, the adhesive layer slurry was obtained.

[0118] The ceramic coating binder polyvinylidene fluoride, ceramic particles alumina (Al2O3), dispersant sodium polyacrylate, thickener carboxymethyl cellulose, and wetting agent fatty alcohol polyoxyethylene ether were mixed in a mass ratio of 23.6:75:0.6:0.5:0.3. The solvent NMP was added, and the mixture was stirred under vacuum until homogeneous to obtain the ceramic coating slurry.

[0119] A 5μm thick polyethylene substrate was used as the diaphragm substrate. A ceramic coating slurry was coated onto the substrate and dried at 80℃ for 1 hour. An adhesive layer slurry was then coated onto the ceramic coating and dried at 80℃ for 1 hour to obtain a single-sided coated diaphragm. The coating weight of the ceramic coating was 1.8 g / m². 2 The areal density of the adhesive layer is 3.5 g / m³. 2 After drying, a diaphragm is obtained.

[0120] Example 2-1

[0121] Except for adjusting the ratio of the adhesive layer slurry to 97.5:1.5:1 in the <Preparation of the diaphragm> section, the rest is the same as in Example 1-1.

[0122] Example 2-2

[0123] Except for adjusting the ratio of the adhesive layer slurry to 99.5:0.3:0.2 in the <Preparation of the Diaphragm> section, the rest is the same as in Examples 1-1.

[0124] Example 2-3

[0125] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as in Examples 1-1.

[0126] Examples 2-4

[0127] Except for adjusting the ratio of ceramic coating slurry to 38.6:60:0.6:0.5:0.3 in the <Preparation of the diaphragm> section, the rest is the same as in Examples 1-1.

[0128] Examples 2-5

[0129] Except for adjusting the ratio of ceramic coating slurry to 4.4:95:0.3:0.2:0.1 in the <Preparation of the diaphragm> section, the rest is the same as in Examples 1-1.

[0130] Examples 2-6 to 2-11

[0131] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as in Examples 1-1.

[0132] Example 2-12

[0133] Except for adjusting the ratio of the positive electrode material layer to 94:2.5:2.5:1 in the <Preparation of Positive Electrode Sheet>, the rest is the same as in Example 1-1.

[0134] Example 2-13

[0135] Except for adjusting the ratio of the positive electrode material layer to 90:2.5:2.5:5 in the <Preparation of Positive Electrode Sheet>, the rest is the same as in Example 1-1.

[0136] Example 2-14

[0137] Except for adjusting the ratio of the positive electrode material layer to 87:2.5:2.5:8 in the <Preparation of Positive Electrode Sheet>, the rest is the same as in Example 1-1.

[0138] Example 2-15

[0139] Except for replacing the type of solid electrolyte with Li in the <Preparation of Positive Electrode> section 1.3 Al 0.3 Ti 1.7 Except for (PO4)3 (LATP), the rest is the same as in Example 1-1.

[0140] Comparative Examples 1 to 3

[0141] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.

[0142] The preparation parameters and performance tests of each embodiment and comparative example are shown in Table 1 and Table 2.

[0143] Table 1

[0144] Note: In Table 1, N is the number of positive electrode layers; ρ is the compaction density of the positive electrode material layer; T is the thickness of the positive electrode material layer; S is the interfacial stress coefficient; I is the ion transport requirement coefficient; and W is the areal density of the binder layer.

[0145] As can be seen from Examples 1-1 to 1-10 and Comparative Examples 1 to 3, by setting an adhesive layer that meets the characteristics of this application in the separator and adjusting the specifications of the positive electrode within the scope of this application, the lithium-ion battery has a high interface peeling force and a high cycle capacity retention rate, and a low DC internal resistance growth rate, indicating that the cycle performance of the embodiments of this application is good. The areal density of the diaphragm adhesive layer in Comparative Examples 1 and 2 does not meet the characteristics of this application. Specifically, the areal density of the diaphragm adhesive layer in Comparative Example 1 is too high, and the areal density of the diaphragm adhesive layer does not match the compaction density ρ, thickness T, and number of layers N of the positive electrode sheet, resulting in a lower cycle capacity retention rate and a higher DC internal resistance growth rate. The areal density of the diaphragm adhesive layer in Comparative Example 2 is too low, and the areal density of the diaphragm adhesive layer does not match the compaction density ρ, thickness T, and number of layers N of the positive electrode sheet, resulting in poor interfacial peel strength. The specifications of the positive electrode sheet in Comparative Example 3 do not meet the characteristics of this application. Specifically, the number of positive electrode sheet layers, the compaction density of the positive electrode material layer, and the thickness of the positive electrode material layer in the specifications of Comparative Example 3 are all less than the range of this application, resulting in poor interfacial peel strength and a higher DC internal resistance growth rate. This indicates that comparative examples not within the scope of this application have lower interface peeling force, lower cycle capacity retention rate, and higher DC internal resistance growth rate, while embodiments of this application have higher interface peeling force, higher cycle capacity retention rate, and lower DC internal resistance growth rate. This demonstrates that embodiments satisfying the features of this application can improve the adhesion between the electrode and the separator, reduce the DC resistance growth rate of the lithium-ion battery, and improve the cycle performance of the lithium-ion battery.

[0146] As can be seen from Examples 1-1 to 1-9, the interfacial stress coefficient and ion transport demand coefficient affect the adhesion between the electrode and the separator, the DC resistance growth rate of the lithium-ion battery, and the cycle performance of the lithium-ion battery. When the values ​​of S and I are adjusted within the above ranges, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0147] As can be seen from Examples 1-1, 1-6 to 1-9, the areal density of the adhesive layer affects the adhesion between the electrode and the separator, the DC resistance growth rate of the lithium-ion battery, and the cycle performance of the lithium-ion battery. When the value of W is adjusted within the above range, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0148] As can be seen from Examples 1-1 and 1-10, the placement of the separator coating affects the adhesion between the electrode and the separator, the DC resistance growth rate of the lithium-ion battery, and the cycle performance of the lithium-ion battery. In Examples 1-10, the ceramic coating and adhesive layer of the separator are only placed on the side facing the positive electrode. Compared with Examples 1-1, both exhibit higher capacity retention after 1000 cycles and lower DC internal resistance growth rate. This indicates that the embodiments satisfying the features of this application can reduce the DC resistance growth rate of the lithium-ion battery and improve the cycle performance of the lithium-ion battery while maintaining high adhesion between the electrode and the separator.

[0149] Table 2

[0150] Note: In Table 2, w1 represents the mass percentage of the binder; w3 represents the mass percentage of the ceramic particles; φ2 represents the porosity of the substrate; w2 represents the mass percentage of the carbon material layer; w4 represents the mass percentage of the solid electrolyte; and φ1 represents the porosity of the diaphragm.

[0151] As can be seen from Examples 1-1, 2-1 to 2-2, the mass percentage content of the binder in the adhesive layer affects the DC resistance growth rate and cycle performance of the lithium-ion battery. When the value of w1 is adjusted within the above range, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high bonding force between the electrode and the separator.

[0152] As can be seen from Examples 1-1 and 2-3, the type of binder affects the DC resistance growth rate and cycle performance of the lithium-ion battery. When the type of binder in the adhesive layer is controlled within the above-mentioned range, the lithium-ion battery exhibits a higher capacity retention rate after 1000 cycles and a lower DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high bonding force between the electrode and the separator.

[0153] As can be seen from Examples 1-1, 2-4 to 2-6, the type and mass percentage of ceramic particles in the ceramic layer affect the DC resistance growth rate and cycle performance of the lithium-ion battery. When the type of ceramic particles and the value of w3 are controlled within the above range, the lithium-ion battery exhibits a higher capacity retention rate after 1000 cycles and a lower DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0154] As can be seen from Examples 1-1, 2-7 to 2-9, the porosity of the substrate affects the adhesion between the electrode and the separator, the DC resistance growth rate of the lithium-ion battery, and the cycle performance of the lithium-ion battery. When the value of φ2 is adjusted within the above range, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0155] As can be seen from Examples 1-1, 1-6 to 1-9, and 2-7 to 2-9, the porosity of the separator affects the adhesion between the electrode and the separator, the DC resistance growth rate of the lithium-ion battery, and the cycle performance of the lithium-ion battery. When the value of φ1 is adjusted within the above range, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0156] As can be seen from Examples 1-1, 2-10 to 2-11, the mass percentage content of the carbon material layer affects the DC resistance growth rate and cycle performance of the lithium-ion battery. When the value of w2 is adjusted within the above range, the lithium-ion battery exhibits a high capacity retention rate after 1000 cycles and a low DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining high adhesion between the electrode and the separator.

[0157] As can be seen from Examples 1-1, 2-12 to 2-15, the type and mass percentage of the solid electrolyte affect the DC resistance growth rate and cycle performance of the lithium-ion battery. When the weight of the solid electrolyte and the value of w4 are controlled within the above range, the lithium-ion battery exhibits a higher capacity retention rate after 1000 cycles and a lower DC internal resistance growth rate. This indicates that the embodiments provided in this application can reduce the DC resistance growth rate of the lithium-ion battery and improve its cycle performance while maintaining a high adhesion between the electrode and the separator.

[0158] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.

[0159] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A secondary battery, characterized in that, The assembly includes an electrode assembly comprising a positive electrode sheet and a separator; the positive electrode sheet has N layers along its thickness direction, where 20 ≤ N ≤ 85, and includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector, wherein the compaction density of the positive electrode material layer is ρ g / cm³. 3 2.2≤ρ≤2.8, the thickness of the positive electrode material layer is T μm, 20≤T≤180; the separator includes a substrate and an adhesive layer disposed on at least one surface of the substrate, the areal density of the adhesive layer is W g / m³. 2 ; Satisfy: S=ρ×ln(N+1)×T, I=1 / (ρ×T), 0.00167S+0.0167I+0.0167≤W≤0.005S+0.067I+0.05; Where S is the interfacial stress coefficient and I is the ion transport demand coefficient.

2. The secondary battery according to claim 1, characterized in that, It meets at least one of the following characteristics: (1)344≤S≤1780; (2)0.002≤I≤0.009; (3)0.9≤W≤6。 3. The secondary battery according to claim 1, characterized in that, The porosity of the diaphragm is φ1, 20%≤φ1≤60%.

4. The secondary battery according to claim 1, characterized in that, The adhesive layer includes an adhesive, which includes at least one of polyvinylidene fluoride, polymethyl methacrylate, styrene-butadiene rubber, polyacrylate, or lithium poly(4-styrene sulfonate); based on the mass of the adhesive layer, the mass percentage of the adhesive is w1, 97.5% ≤ w1 ≤ 99.5%.

5. The secondary battery according to claim 1, characterized in that, The positive electrode material layer includes a positive electrode active material, which includes lithium iron phosphate. At least a portion of the surface of the lithium iron phosphate is provided with a carbon material layer. Based on the mass of the lithium iron phosphate, the mass percentage of the carbon material layer is w2, where 0.5% ≤ w2 ≤ 2.5%.

6. The secondary battery according to claim 1, characterized in that, The diaphragm includes a ceramic coating disposed on at least one side surface of the substrate, the ceramic coating being located between the adhesive layer and the substrate.

7. The secondary battery according to claim 6, characterized in that, The ceramic coating comprises ceramic particles, which include at least one of alumina, boehmite, silicon oxide, magnesium oxide, titanium oxide, calcium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate; based on the mass of the ceramic coating, the mass percentage of the ceramic particles is w3, 60% ≤ w3 ≤ 95%.

8. The secondary battery according to claim 1, characterized in that, The positive electrode material layer includes a solid electrolyte, which includes at least one of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, or lithium titanium aluminum phosphate; based on the mass of the positive electrode material layer, the mass percentage of the solid electrolyte is w4, where 1% ≤ w4 ≤ 5%.

9. The secondary battery according to claim 1, characterized in that, The porosity of the substrate is φ2, 30%≤φ2≤70%.

10. An electronic device, characterized in that, The secondary battery includes any one of claims 1 to 9.

Citation Information

Patent Citations

  • Diaphragm and lithium ion battery comprising same

    CN113363670A

  • Environment-friendly and energy-saving preparation process of water-based low-impedance electrode

    CN118173719A